Rendering Gigaray Light Fields. (6th May 2013) - Birklbauer, C.; Opelt, S.; Bimber, O.
Abstract: We present a caching framework with a novel probability‐based prefetching and eviction strategy applied to atomic cache units that enables interactive rendering of gigaray light fields. Further, we describe two new use cases that are supported by our framework: panoramic light fields, including a robust imaging technique and an appropriate parameterization scheme for real‐time rendering and caching; and light‐field‐cached volume rendering, which supports interactive exploration of large volumetric datasets using light‐field rendering. We consider applications such as light‐field photography and the visualization of large image stacks from modern scanning microscopes.